The care center influences the management of lymphoma patients in a universal health care system: an observational cohort study. Issue 1 (December 2016) - Lamy, S.; Bettiol, C.; Grosclaude, P.; Compaci, G.; Albertus, G; Récher, C.; Nogaro, J.; Despas, F.; Laurent, G.; Delpierre, C.
Abstract Background Healthcare providers-related disparities in adherence to the treatment plan among lymphoma patients are found even in a universal healthcare system, but the mechanism remains unclear. We investigated the association between the type of care center and the relative dose intensity and determined whether it persists after adjustment for patients' recruitment differences. Methods Prospective observational cohort study of 294 patients treated with standard protocols for diffuse large B-cell lymphoma (DLBCL) in teaching or community public hospitals or in private centers in the French Midi-Pyrénées region from 2006–2013. To test our assumptions, we used multinomial and mixed-effect logistic models progressively adjusted for patients' biomedical characteristics, socio-spatial characteristics and treatment-related toxicity events. Results Patients treated using standard protocols in the teaching hospital had more advanced stage and poorer initial prognosis without limitation regarding the distance from the residence to the care center. Patients' recruitment profile across the different types of care center failed to explain the difference in relative dose intensity. Low relative dose intensity was less often observed in teaching hospital than elsewhere. Conclusion We showed that even in a universal healthcare system, disparities in the management of DLBCL patients' do exist according to the types of care center. A main issue may be to find and diffuse the reasons of this benefit in cancer management in the teaching hospital to the other centers.